Penerapan Pendekatan Realistic Mathematic Education Untuk Meningkatkan Konsep Diri (Self Concept) Siswa SMP di Era Milenial - Ridwan Sopyan; Mira Kurnia Dewi; Gagan Aditya Fauzan; Martin Bernard (Departement of Mathematics Education, 2019)
This research was conducted at SMPN 02 Kersamanah VIII. This research is a Posstest-only Control Design in which the researcher only compares the results of the posttest of the experimental class and the control class. The purpose of this study was to determine differences in the ability of students 'mathematical self-concept between classes where learning uses the RME approach and classes that use conventional approaches and strengthen students' self-concepts in the millennial era. This study used 25 experimental and control class students as samples with a duration of research consisting of 8 meetings. Based on the analysis of post-test data and N-Gain shows that there are significant differences in the ability to think logically mathematically where the mathematical self-concept of students whose learning using the RME approach is better than the classroom learning using conventional approaches. This is because the use of the RME approach provides meaningful learning by seeing, searching, and exploring real objects. Where students have more responsibility for learning mathematics, reducing online gaming activities, and the use of gadgets.